QOL-40. RADIATION DOSE EFFECT ON NEUROPSYCHOLOGICAL OUTCOME OF POSTERIOR FOSSA BRAIN TUMOR SURVIVORS. Issue 2 (22nd June 2018) - Tanedo, Jeffrey; O'Neil, Sharon; Huft, Katrina; Tondulkar, Aditi; Wong, Kenneth; Olch, Arthur; Malvar, Jemily; Maina, Katherine; Tsao, Sinchai; Lepore, Natasha; Nelson, Mary Baron
Abstract: Children with brain tumors treated with cranial irradiation experience significant cognitive late effects. Cranial irradiation followed by posterior fossa boost results in high doses of radiation to the thalamus, hippocampus and putamen, structures critical to cognitive functioning. Twenty-three children (mean 12 years of age) with a history of posterior fossa tumor (13 treated with surgery, chemotherapy and cranial irradiation; 10 treated with surgery and chemotherapy) underwent neuroimaging, neurocognitive and psychosocial assessment 3.7 to 8.8 years after treatment. The putamen, thalamus and hippocampus were manually segmented in the radiation treatment group and the dose to each structure was calculated. Differences in patient demographics and medical history among patients in each treatment group were evaluated using the χ 2 test (for categorical variables) and t-test (for continuous variables). Linear regression was utilized to examine differences in neuropsychological test scores and QOL measures among the two treatment groups. Time off treatment was a significant predictor of verbal comprehension standard index score and BRIEF ® metacognition index for survivors in both treatment groups, before correction for multiple comparisons. There were no significant differences on psychometric scores between the two groups after Bonferroni correction, and no significant correlation of structural radiation dose to scores; however, there was wide range of abilities from impaired to superior in both groups in this small sample.